Technology and productivity : the Korean way of learning and catching up - Lim, Youngil (MIT Press, 1999)
"In this book Youngil Lim explores the process by which the poverty-stricken agrarian economy of South Korea was transformed over the past three decades into a semi-industrial urban economy. The chief questions Lim addresses are: Where did South Korea's technological knowledge come from? What did the government and market do to nurture such rapid learning? Will a continuation of current policy enable South Korea to catch up with other OECD countries? What is the appropriate role of the National Research and Development Program within the framework of the National System of Innovation?"--BOOK JACKET.